Texture Profile and Pectinase Activity in Tomato Fruit (Solanum Lycopersicum, Servo F1) at Different Maturity Stages and Storage Temperatures - Gebregziabher, Angesom Asgele; Supriyadi, Supriyadi; Indarti, Siwi; Setyowati, Lilis (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
The demand for daily consumption of tomato fruit is increasing immensely. Nevertheless, the fruit is exposed to mechanical damage, shrinking, and softening as the maturity stages, handling, and storage are inappropriate, thereby affecting the texture. The study aimed to assess the texture profile, pectinase activity, and physicochemical parameters in tomato fruit at different maturity stages and storage temperatures. The fruits were harvested at 1-4 weeks after pollination and stored at a temperature of 16 ºC and 25ºC. There was an increase in the redness color (a*), TSS content, weight loss, respiration rate, and ethylene production, while the hardness, lightness color (L*), pH, and TA decreased with an increase in maturity stages at different storage temperatures. The higher Polygalacturonase (PG) and Pectin methylesterase (PME) enzyme activities were observed at 25 ºC compared to storage temperature of 16 ºC. It was confirmed that pectinase activity extremely affected the texture profile. For commercial purposes, it is suggested that tomatoes are harvested at 2nd and 3rd week after pollination for long distance transportation and at 4th week for fresh consumption and stored at a temperature of 16 °C.